Understanding science-in-the-making by letting scientific instruments speak: From semiotics to postphenomenology. (June 2021) - de Boer, Bas; te Molder, Hedwig; Verbeek, Peter-Paul
Latour encourages us to use science-in-the-making as an entry point to understanding science, because it allows us to see how scientific knowledge is constituted and through which processes the 'absolute certainties' of ready-made science appear. He approaches science-in-the-making from the perspective of semiotics because it enables him (1) to attribute equal importance to humans and nonhumans, and (2) to let the actors in scientific practices speak for themselves. We argue that Latour's semiotic approach to science-in-the-making and his understanding of scientific instruments as inscription devices do not fulfill these desiderata. This, in turn, prevents him from understanding the crucial role that scientific instruments play in science-in-the-making. As an alternative to Latour's semiotic approach, we present a postphenomenological approach to studying science-in-the-making. Using the notion of technological mediation, we argue that scientific instruments actively mediate how reality becomes present to – and is treated by – scientists. Focusing on how intentional relations between scientists and the world are mediated by scientific instruments makes it possible to turn them into genuine actors that speak for themselves, thereby recognizing their constitutive role in the development of the interpretational frameworks of scientists. We then show how a postphenomenological approach can be understood as an ethnomethodology of human-technology relations that meets both of Latour's requirements when studying science-in-the-making.